Construction of TiO2@Cu2O-CuS heterostructures integrating RGO for enhanced full-spectrum photocatalytic degradation of organic pollutants - Andronic, Luminita; Abreu-Jaureguí, Coset; Silvestre-Albero, Joaquin (Elsevier B.V., 2024)
This study presents the development and optimization of TiO2@Cu2O-CuS heterostructures, enhanced with reduced graphene oxide (RGO), for efficient photocatalytic degradation of organic pollutants, focusing on imidacloprid. Two configurations, TiO2/RGO/Cu2O-CuS and Cu2O-CuS/RGO/TiO2, are explored to highlight the impact of material layering on photocatalytic efficiency. The strategic integration of RGO optimizes charge transfer, crucial for photocatalysis. Comprehensive characterization techniques, such as X-ray diffraction (XRD), Transmission Electron Microscopy (TEM), X-ray Photoelectron Spectroscopy (XPS), Raman spectroscopy, and Nitrogen adsorption-desorption isotherms, provide insights into the crystalline structure, morphology, surface chemistry, and textural properties of the heterostructures. The TiO2/RGO/Cu2O-CuS configuration significantly outperforms its counterpart in photocatalytic activity under full-spectrum (UV–VIS–IR) illumination, due to improved charge carrier dynamics and synergistic interactions between the composite materials. Remarkably, the TiO2/RGO/Cu2O-CuS assembly achieved over 95 % degradation of imidacloprid under simulated solar irradiation, marking a breakthrough in solar spectrum utilization for photocatalysis and exhibits promising recyclability, maintaining its high photocatalytic efficiency even after multiple degradation cycles, highlighting its potential for sustainable pollutant removal applications. Additionally, this configuration demonstrates a twofold increase in degradation efficiency compared to separate UV and VIS irradiations, emphasizing its rapid pollutant removal capability. This research underscores the critical role of material layer sequencing in developing high-efficiency photocatalytic systems and marks a significant advancement in environmental remediation technologies that harness renewable energy sources.
Keywords: TiO2@Cu2O-CuS heterostructures; Reduced graphene oxide; Full-spectrum photocatalysis; Imidacloprid degradation; Nanocomposite engineering; Environmental remediation